Transforming laboratory management learning with e-modules - Mirah Surya Dewi, Ni Pt. Pande; Liska, Luh De; Parwati, Ni Putu Yuniarika (Indonesian Journal of Educational Development (IJED), 2025)
Laboratories are crucial in chemistry education; however, in practice, many students still struggle to grasp the concept of laboratory management in an applied way, as reflected in their scores, which remain below the passing grade. This research aimed to develop e-modules based on case-based and project-based learning to improve understanding of laboratory management concepts. This study used a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Validation of e-modules was carried out by material and media experts, and tested on 24 FKIP ULM Chemistry Education students. Data collection instruments included validation questionnaires, student response questionnaires, as well as pretests and posttests, which were analysed using the Wilcoxon test. The results showed that the e-module was rated “very valid” from the aspects of content, presentation, language, and media. The Wilcoxon test resulted in a significance value of 0.000 (p < 0.05), indicating a significant increase in student concept understanding after the use of e-modules. Recommendations from this study are the wider use of case- and project-based e-modules in learning laboratory management, as well as continuous development to be more adaptive to the development of educational technology.